Determination of chlorine in solid fuels using an improved Eschka method - Rahim, Usman; Gao, Xiangpeng; Wu, Hongwei (Elsevier Ltd, 2014)
Conventional Eschka method is a standard method for the determination of chlorine (Cl) in solid fuels. However, the method significantly underestimates the Cl contents in some low-rank solid fuels (e.g., biomass) due to the escape of Cl with flue gas from the Eschka combustion process. An improved Eschka method is developed to recover the escaped Cl in the flue gas via converting it into HCl(g) by flue gas re-combustion for capture and quantification. The improved Eschka method can accurately quantify Cl in a range of solid fuels studied (i.e., a mallee bark, a Victorian brown coal, a sub-bituminous coal, an anthracite coal, and a polyvinyl chloride), with a small relative standard error (±2%) and a low limit of quantification (0.015 mg/g fuel, dry basis) under present experimental conditions.